Artistic Reconstruction of the Great Patriotic War in Modern Mass Literature - T. N. Markova (Научный диалог)
Variants of artistic reconstruction of the events of the Great Patriotic War in modern mass literature are considered. The material is multi-genre texts of the 2000s: an alternative version of the history of the Great Patriotic War, free-thinking fantasies in a mystical spirit, a postmodern historical melodrama, a fantasy novel, a military-fantasy action movie. Particular attention is paid to the national bestsellers of the 2000s: novels by A. Turgenev (V. Kuritsyn) “Sleep and Believe: Blockade novel” and I. Boyashov “Tanker, or “The White Tiger.” It is shown that A. Turgenev in his work combines the legends of the besieged time with the cliches of a spy novel and love melodrama, I. Boyashov is the author of the story of the duel of a Russian tanker and a German miracle tank in the form of modern fantasy. The article affirms the idea that with the leave of the generation of front-line soldiers, the war moves from living memory into a repository of plots and images for literature and art, and becomes fertile material for constructing a different reality. It is hypothesized that mass literature, reconstructing the facts and events of the recent past, is involved in modeling and rethinking the ideological and value orientations of society and the formation of a new identity.